Block periodization programming: Efficacy in subjects of differing strength levels - Moquin, P. (East Tennessee State University, 2021)
Physiological muscle adaptations due to resistance training are still not fully known. The rate and area of hypertrophy could drastically help or hinder athletic performance. The purpose of this study was to observe the changes in lean body mass (and related factors), relative allometrically scaled strength and absolute strength through an 11-week block periodized resistance training program. The subjects (n = 15) realized an increase in total body water (pre = 49.77Kg; post = 51.70Kg), lean body mass (pre = 67.98Kg; post = 70.63Kg), adjusted lean body mass (pre = 20.35Kg; post = 21.03Kg) and cross sectional area (pre = 32.73 cm2; post = 36.33cm2). Subjects (n= 15) were divided into either a strong (1 RM = 1.75x body weight), moderate (1 RM = = 1.25-1.74x body weight), or weak (1 RM < 1.25x body weight) group and data were analyzed in pre-post training. While all subjects showed gains in LBM and related factors, initial strength levels altered these adaptations. Subjects with a lower initial maximum strength level tended to make greater gains. However, due to the increase in total body water and relatively small increases in adjusted LBM, it appears, among this group, that little myofibrillar hypertrophy occurred during this short training period. These data suggest that greater accuracy for measures of alterations in LBM and related factors may require measures of total body water.